Academic Stress Among Nursing Students in Medan - Tumanggor, Roxsana Devi; Jamilah, Ummu (Caring: Indonesian Journal of Nursing Science, 2022)
Stress occurs when a stressor stimulates an individual's brain and leads to physical and psychological symptoms. Students must deal with some stressors in their studies that cause a high complexity of problems. Furthermore, in some cases, it leads to some academic stress. This study aims to describe the academic stress of the Nursing Students of the Faculty of Nursing, Universitas Sumatera Utara. This research is a descriptive study with a cross-sectional approach. The population in this study were all undergraduate nursing students, totalling 574 people, with a sample of 85 people using the proportionate stratified random sampling technique. All samples are obtained with the Slovin formula and recruited with the sweepstake technique in every class. Data analysis was conducted to determine the frequency distribution of the variables studied. The results showed that there were 35 students without academic stress (41.2%), 47 students with mild academic stress (55.3%), and three students with moderate academic stress (3.5%). Based on the study results, it is recommended that further researchers need to conduct further exploration of student academic stress in qualitative studies.